Stability and change through time in the dialects of a Neotropical songbird, the Rufous-collared Sparrow - García, Natalia Cristina (2016)
Behavioural characters that are learned can show temporal variation due to changes in a population across generations that are not due to changes in the same individual. The song of the Rufous-collared Sparrow, Zonotrichia capensis, shows significant geographic variation associated with habitat vegetation, defining song dialects. To study the temporal stability or change of Rufous-collared Sparrow dialects at a microgeographical scale, we compared the recordings made in Estancia ?El Destino? (in the northeast coast of Buenos Aires province, Argentina) during 1987 and 2000 with a set of recordings made during 2010 and 2011. We found that the dialect boundaries of the Rufous-collared Sparrow remained stable over a period of 24 years. Since we did not detect gross changes in the habitat characteristics, we concluded that habitat structure is an important factor for dialect distribution. When we consider each dialect separately, the variation detected in some traits between 1987 and 2000 persisted while other traits showed reversal across time. These findings are consistent with the hypothesis that some changes in song were the result of neutral variation, whereby changes due to random factors such as copying error, for example, could have been maintained or introduced across generations.